Analysis of Characteristics of Rice Husk Briquettes Using Starch Adhesive with Varying Adhesive Percentages - Alfian, Devia Gahana Cindi; Yunasdi, Hamda; Syaukani, Muhammad; Silitonga, Dicky Januarizky (Simetris: Jurnal Teknik Mesin, Elektro dan Ilmu Komputer, 2024)
The increasing energy demand is currently being experienced by many countries, including Indonesia. Biomass holds significant potential as an alternative energy source that can replace the widely used fossil fuels. Biomass is also available in abundant quantities. One method to harness energy from biomass is through briquetting. Briquettes are solid materials that can be used as fuel for a specified period. In this research, rice husk biomass is used as the primary material for creating briquettes. Tapioca flour is used as the binder, and the briquettes are formed under a pressure of 40 kg/cm². The drying process is carried out at a temperature of 100°C for 3 hours, with variations in the percentage of the binder. The binder-to-rice husk ratios tested are 70% + 30%, 60% + 40%, and 50% + 50%. Based on the conducted tests, the most favorable variation is the briquette with a 50% + 50% adhesive-to-rice husk ratio. This variation exhibits a moisture content of 4.84%, a calorific value of 26,728.61 cal/g, an ash content of 28.78825%, a carbon content of 50.427%, a volatile matter content of 33.919%, and a combustion rate of 0.45662 g/minute.